2014
DOI: 10.1002/erv.2311
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction in a Spanish Sample of Eating Disorders: DSM‐5 Diagnostic Subtype Differentiation and Validation Data

Abstract: Although the concept of 'food addiction' (FA) has raised growing interest because of evidence for similarities between substance dependence and excessive food intake, there is a lack of studies that explore this construct among the wide spectrum of eating disorders (EDs). Besides providing validation scores of a Spanish version of the Yale FA Scale (YFAS-S), this study examined the prevalence of 'FA' among ED subtypes compared with healthy-eating controls (HCs) and the association between 'FA' scores, eating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
141
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(173 citation statements)
references
References 44 publications
(63 reference statements)
24
141
4
4
Order By: Relevance
“…The higher YFAS 2.0 ‘food addiction' prevalence among underweight individuals is unexpected, though consistent with previous work [29]. Notably, in the current study, all three participants with underweight were in the youngest age range (18-29 years old), and their BMIs are within the range for anorexia nervosa according to the DSM-5 [40].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The higher YFAS 2.0 ‘food addiction' prevalence among underweight individuals is unexpected, though consistent with previous work [29]. Notably, in the current study, all three participants with underweight were in the youngest age range (18-29 years old), and their BMIs are within the range for anorexia nervosa according to the DSM-5 [40].…”
Section: Discussionsupporting
confidence: 75%
“…Among persons with obesity, the occurrence of ‘food addiction' will be higher compared to those with normal weight [23]. The authors furthermore hypothesize that the occurrence of ‘food addiction' is higher among underweight individuals, compared to those with normal weight, as one previous study observed that ‘food addiction' prevalence is elevated in eating disorders associated with underweight (e.g., anorexia nervosa) [29]. Consistent with previous literature, we expect that ‘food addiction' will be more prevalent among women [22,24,25] and negatively related to age [38].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The lowest scores on the YFAS were associated with the restrictive subtype of AN and the highest ones with the subtypes of ED associated with binge eating: purging AN (85.7%), BN (81.5%), and BED (76.9%). Higher YFAS scores were also associated with higher levels of negative affect, depressive symptoms, higher BMI, more severe eating pathology, and general psychopathology [44].…”
Section: Does Food Addiction Exist?mentioning
confidence: 89%
“…26 La YFAS se ha utilizado en numerosos estudios y las traducciones de sus versiones en alemán, francés y español (aplicado en España) ya han sido validadas obteniendo un α de Cronbach de 0.81 -0.83, 0.90 y 0.82, respectivamente. [27][28][29][30][31] Se ha desarrollado también una versión corta de la escala, misma que comprende únicamente nueve ítems, uno para cada aspecto conductual de la adicción (siete ítems) más dos ítems para evaluar manifestaciones clínicas significativas (α = 0.75-0.84). 32 Así mismo, existe una versión de la escala adaptada para niños (α = 0.78).…”
unclassified